Dynamic Governance Model for Mass Rapid Transportation in Jakarta - Amin, Chair; Wicaksana, Harits Hijrah (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to investigate the Dynamic Governance Model in Jakarta's Mass Rapid Transportation (MRT) system. The fundamental principle of Dynamic Governance is the integration of culture and capability to foster change that aligns with evolving societal needs in an era marked by uncertainty. Organizations must dynamically and flexibly adapt to effectively navigate the complexities they face. A qualitative approach was employed in this research, utilizing data collection methods such as interviews, observations, and document analysis. The findings reveal that the implementation of the three pillars of Dynamic Governance is consistently preceded by preparatory processes. For example, research is conducted prior to the application of thinking ahead, internal reviews precede thinking again, and benchmarking is undertaken before implementing thinking across. Additionally, the study identifies interconnections among the three pillars, emphasizing their mutual reinforcement. Furthermore, culture is found to play a vital role in fostering work commitment and ensuring operational consistency in the field.